Molecular Pathogenesis of Human Rhinovirus (HRV) Infection - Murti, Anissa Wari; Andi Yasmon (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2024)
Human Rhinovirus (HRV) is a RNA virus belonging to the Picornaviriade family that most often causes acute respiratory infections (ARI). This virus can cause dangerous infections in children, people with chronic respiratory disorders, and individuals with low immunity. This virus can infect newborns six to eight Â times and adults two to four times per year. In addition, HRV is the main cause of pneumonia and bronchiolitis which can worsen the symptoms of cystic fibrosis asthma. This article also discusses the development of the HRV replication process that occurs in the respiratory tract epithelium which takes place in several stages, starting with virus attachment and ending with the release of new virions. We also analyze the stages of neutralizing antibodies (nAbs) to prevent HRV infection. Currently, there are not any authorized antiviral drugs or HRV vaccination because this virus has highly variable antigenic sites. To develop a vaccine that can protect against various HRV serotypes, a consensus sequence that combines several strains is needed.